Active immunisation of human interferon α transgenic mice with a human interferon α Kinoid induces antibodies that neutralise interferon α in sera from patients with systemic lupus erythematosus. Issue 6 (9th March 2011) - Mathian, Alexis; Amoura, Zahir; Adam, Estelle; Colaone, Fabien; Hoekman, Marco F M; Dhellin, Olivier; Vandepapelière, Pierre; Haroche, Julien; Piette, Jean-Charles; Lebon, Pierre; Grouard-Vogel, Géraldine
Abstract : Objectives: Interferon α (IFNα) plays a central role in the pathogenesis of systemic lupus erythematosus (SLE) and is considered a target for its treatment. In the current study, the ability of active immunisation with a human (hu) IFNα2b Kinoid (IFN-K) to break B cell tolerance to IFNα and to induce huIFNα-neutralising antibodies in mice immunotolerant to huIFNα2b was assessed. Methods: IFN-K was manufactured by crosslinking huIFNα2b to keyhole limpet haemocyanin (KLH). Transgenic mice expressing huIFNα2b received by intramuscular injection either saline or polymerised huIFNα2b as controls, or IFN-K, emulsified in ISA51vg adjuvant. Results: All of the huIFNα2b-expressing mice immunised with IFN-K generated neutralising antibodies against huIFNα2b. In addition, these antibodies neutralised all 13 subtypes of huIFNα. They also neutralised IFNα activity in sera collected from 10 different patients with active SLE. However, the antibodies did not bind to huIFNγ or huIFNβ. Finally, cellular activation assays showed that immunisation with IFN-K did not induce memory T cells reactive to native huIFNα2b, whereas it did induce memory cells reactive to KLH. Conclusion: These results show that active immunisation with IFN-K induces polyclonal antibodies that neutralise all subtypes of huIFNα as well as IFNα in sera from patients with SLE by breaking humoral but not cellular tolerance to IFNα. This suggests that immunisation with IFN-K is a promising new therapeutic strategy for the treatment of SLE.